INJECTIONS VS ORAL ANABOLIC STEROID WHICH CORRELATIONSHIP EXPLAIN THE DOPING RISKS HEALTH IN THE LEISURE ALGERIAN SPORT BODYBUILDING - Bengoua, Ali; Zerf, Mohammed; Mokkedes, Moulay Idris; ATTOUTI, NOUREDINE; ANDRE, SEABRA (https://www.researchgate.net/publication/283210301_INJECTIONS_VS_ORAL_ANABOLIC_STEROID_WHICH_CORRELATIONSHIP_EXPLAIN_THE_DOPING_RISKS_HEALTH_IN_THE_LEISURE_ALGERIAN_SPORT_BODYBUILDING?_sg=PvtHCpiPQw2-Q-4M8YQ8F-SihyrnpfsxF7dB0yjzWEvdZhmxzZVYXS5tP8-CB0nt5zzQ4LAZhFSeQbIXjPf0Wdz4WQi5aZScj0VPtF5-.Pbth4uPsO44zv3O-w_nySH-9-epfr01oQ-CCNPmU-7KC6vt7aCRpbJnNTb3Yrfv76_33DzOT54nyMKoBrirxOw, 2015)
Accordingly, to the literature reviewer, the anabolic steroids evolved throughout the 1980s as public attention, where this practice is believed to increase the total anabolic steroid concentrations and their effects on the body while reducing the toxic effects on the liver and early kidney dysfunction. Seen anabolic steroids evolved as public attention, as for our Leisure Algerian Sport Bodybuilding the purposes of this study were to expose the dangers of anabolic steroids as chemical supplies Injections or oral including as anabolic steroids in the practice of Algerian Bodybuilders that seek an increase in muscle mass. From that, our samples are consisted from Ten Algerian amateur athletes where their homogeneity was based on (≥18 years; 5 years of bodybuilder practice), and the volunteered participated to the experience based on the difference practice doping. Where five athletes included in their training practice injections anabolic steroids whereas other five athletes incorporated in their nutrition. As to study the correlationship that explain the healthy Risks of the two practice we have chosen the Analysis of blood, [1]Measuring the ratio of urea in the blood [2]Measurement of Creatinine in the blood[3]Measure the ratio of testosterone in the blood[4]Blood glucose measurement from two month of their practice. For that, we have chosen the analysis of T-TEST independent and correlation of the volunteer practiced to compare the implementation modification in the regulation of the vital functions. Based on the limits of the study and results accuses in two months we confirm: •The both practices destabilizes the regulation of vital functions •There is a strong correlation between the two practices in all comparisons within the same test •The great risk is in relation concentration urine & creatinine followed by the decrease in testosterone and increase of glucose
Keywords: Doping Anabolic Steroids Injections VS Oral, Risks, Algerian Bodybuilder